Da percepção à ação: uso da água por alunos do ensino fundamental no Colégio da Polícia Militar (CPM) unidade IX Custódia da Silva Pedreira em Porto Nacional – TO, Brasil - Neto, Janaina Nogueira (Universidade Federal do Tocantins, 2023)
The waste of drinking water is one of the factors that may favor the feared scarcity of this resource and has become a cause of concern for the maintenance of human survival. Thus, its rational use can be education-oriented. Environmental Education can be developed in various social gatherings, and especially in school. Thus, the objective of this work is to understand the perception that elementary school students have about water through their use in school. It is a descriptive research based on observation and bibliographical readings related to the theme. Methodological instruments were applied structured questionnaire with objective questions about water use in school, where the results were tabulated, analyzed and discussed. The study revealed the need for students to continue deepening their knowledge about water use and avoiding waste, so that they feel responsible for preserving this resource beyond school.